Enhanced Yield of Methyl Ethyl Ketone through Levulinic Acid Decarboxylation in the AgNO3/K2S2O8 System: Mechanistic Insights and Characterization of Metallic Species - Nydia I. Guzmán Barrera; Jérôme Peydecastaing; Jérôme Esvan; Joël Albet; Carlos Vaca-Garcia; Philippe Behra; Emeline Vedrenne; Sophie Thiébaud-Roux (Molecules, 2024)
Methyl ethyl ketone (MEK) is among the most extensively utilized solvents in various industrial applications. In this study, we present a highly efficient synthesis route for MEK via the decarboxylation of biomass-derived levulinic acid, using potassium persulfate (K2S2O8) and silver nitrate (AgNO3) as key reagents. The specific roles of AgNO3 and K2S2O8 were thoroughly investigated. Additional silver species, such as Ag2O and AgO, were also detected during the reaction. X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analyses provided evidence of the evolution of solid phases throughout the reaction. Based on these findings, we propose a radical decarboxylation mechanism initiated by the generation of sulfate radicals (SO4•⁻) through the catalytic breakdown of K2S2O8 by AgNO3. This mechanistic understanding, combined with a parametric study, enabled us to achieve an unprecedented level of levulinic acid conversion (97.9%) and MEK yield (86.6%) with this system, surpassing all previously reported results in the literature.